At the Cutting Edge Between Semiology And Phenomenology: The Bloody Performances of Orlan and Franko B - Chrysochou, Panayiota (Leitura Flutuante, 2013)
This paper sets out to explore the intricacies between trauma, performance and the body through an in-depth analysis of the various ‘performances’ and ‘rehearsals’ of the French performance artist Orlan and the Italian artist Franko B. Through the lens of psychoanalytical, semiological and socio-theoretical frameworks, and via recourse to trauma and performance studies, it attempts to trace the widespread and obsessive fascination with the tearing and ripping apart of skin. It also draws on Baudrillard’s work on the postmodern, Derrida, and Judith Halberstam’s work on the Gothic, amongst others, to cement its arguments.